TIG torch surfacing of nano-particulate hybrid composite layer: development and characterization - Maleque, Md. Abdul (2017)
The multiphase composite layers have been developed in thick surface on low alloy steel by preplacing TiC/hBN hybrid ceramic particles into a shallow melt pool produced on a moving sample using traditional TIG torch melting technique (known as surfacing). Surface layers ranging in thickness from 0.05 to 1.0 mm are formed, the thickness being determined by the process variables of heat input, particles feed rate and gas flow rate. Typical operating conditions employ TIG input energies, preplaced particle amount, gas flow rate and working distance. The hybrid composite layer was investigated by a diversity of techniques, including scanning electron microscopy (SEM), energy-dispersive spectroscopy (EDS) and microhardness testing. This paper discusses the types of surface morphology or multiphase structures which have been produced by preplacing ceramic particles on the substrate of low alloy steels and TIG melting/particle injection process and considers the effect upon these structures developed by different processing parameters which in turn change the mode of dissolution or particle reeling. Special consideration is given to the degree of hardness development on the hybrid particulate composite (TiC/hBN and TiC/Ni-P-hBN) surface layer after re-solidification via TIG torch melting technique. .